GUDEG AND KIMCHI: EXPLORING THE UNIQUENESS OF TRADITIONAL JAVANESE AND KOREAN CUISINE - Sari, Indah Puspita (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
Every society in the world has a traditional cuisine. Traditional cuisine reflects the history, uniqueness, and culture of a society. One example of a traditional cuisine is gudeg from Yogyakarta and kimchi from Korea. Both are traditional cuisines that have been recognized by UNESCO as intangible heritage. The purpose of this research is to compare the similarities and differences between gudeg and kimchi. The method used is qualitative method. The data collection technique is a literature study by reading and understanding from books, journals or articles relevant to the theme. As a result, the similarities between gudeg and kimchi are that they both come from vegetables, are processed for a long time, and become icons of each region. The difference is that the taste, color, and texture of these two dishes are different. In conclusion, these two dishes are created by the adaptation of the community with the environment in which they live by creating traditional foods with distinctive flavors. The contribution of this research provides an understanding of traditional cuisine from various regions.